Expression Profile of Brain Aging and Metabolic Function are Altered by Resveratrol or α-Ketoglutarate Supplementation in Rats Fed a High-Fat Diet - Paulina Szczurek-Janicka; Katarzyna Ropka-Molik; Maria Oczkowicz; Sylwia Orczewska-Dudek; Mariusz Pietras; Marek Pieszka (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to examine the impact of different dietary interventions started at middle age on the metabolic phenotype and gene expression profiling in the hypothalamus. One-year old rats were fed either a control diet, high-fat diet (HFD), HFD supplemented with resveratrol (HFD+RESV), or HFD supplemented with α-ketoglutarate (HFD+AKG). A 6-week HFD feeding led to significant changes in concentrations of plasma glucose, insulin, lipids, and thyroid hormones. Moreover, 32% of the 84 analyzed genes correlated with aging were differentially expressed compared to the control group, with the largest functional class being related to inflammatory response. Dietary RESV ameliorated the changes in plasma glucose, total cholesterol, and triiodothyronine concentrations induced by HFD feeding and significantly downregulated 60% of the surveyed genes compared to the control group, resulting in a major molecular shift compared to HFD alone. In contrast, AKG supplementation did not affect the metabolic phenotype, but prevented the gene expression pattern caused by HFD consumption, mimicking the effects observed in the control group. HFD feeding induces metabolic dysfunction and age-related genetic alterations in the hypothalamus of middle-aged rats, while dietary RESV or AKG may partially retard these effects, even though these compounds act in a different and specific manner.